Hate the Sin, Love the Sinner: Examining the Role of Religiosity on Generation M’s Attitude Toward Purchasing Luxury Counterfeiting Products in Social Commerce - Ali, Saqib; Zahid, Hasan; Khalid, Nadeem; Poulova, Petra; Akbar, Minhas (Frontiers in Psychology, 2022)
Counterfeiting has become a prevalent business worldwide, resulting in high losses for many businesses. Considerable attention has been paid to research an individual attitude toward purchasing luxury counterfeit products in the offline context. However, there is currently lesser-known literature on the given phenomenon in the context of social commerce. Moreover, researchers observed that counterfeiting consumption is associated with consumer ethical values or beliefs. Practitioners and researchers are keen to find those factors that affect consumers' ethical consumption behaviour to reduce pirated products' demand. However, the role of religion in shaping ethical behaviour is less documented in the counterfeiting context. Therefore, this study investigated the effect of religiosity on the Counterfeiting of luxury products in Pakistan. A five-dimensional Islamic religiosity model was adopted to understand the consumption phenomena. For quantitative research, cross-sectional data were collected from the generation M of Pakistan through self-administrative questionnaires. 394 valid responses from active online users were collected to empirically examine the conceptual model by employing the partial least square structural equation model (PLS-SEM). The results reveal that all five dimensions of religiosity negatively affect the attitude of generation M. Moreover, it is found that knowledge has the highest negative effect on attitude, followed by orthopraxis, experience, central duties, and basic duties. The study also explains the theoretical and practical implications of the research. Finally, limitations and future research were also discussed